(untitled) (GYMNASIUM, 2017)
This paper aims to highlight the effects of using the differential treatment in physical education lessons, in pre-university education. Used both as a method and a principle, the differential treatment, although it is far from representing a novelty in motor activities, may acquire, through its specificity, multiple valences. In this research, the differential treatment was used according to the motor potential of pupils included in the study. We achieved an initial testing, which comprised events specific to the evaluation of athletic motor skills, namely the 50 m. speed running with a crouch start, oina ball throwing and running long jump. In the research, three samples were evaluated, they being represented by the 6th, 7th and 8th grades. These were the experiment groups, the control groups missing from our study. After applying the differential programme, we made the final testing, which emphasized the efficiency of using the differential treatment in physical education lessons.